Contrasting diversity patterns of breeding Anatidae in the Northern and Southern Hemispheres. Issue 17 (15th August 2019) - Zeng, Qing; Reid, Julian; Saintilan, Neil; Colloff, Matthew J.; Lei, Guangchun; Wen, Li
Abstract: For sustaining ecosystem functions and services, environmental conservation strategies increasingly target to maintain the multiple facets of biodiversity, such as functional diversity (FD) and phylogenetic diversity (PD), not just taxonomic diversity (TD). However, spatial mismatches among these components of biodiversity can impose challenges for conservation decisions. Hence, understanding the drivers of biodiversity is critical. Here, we investigated the global distribution patterns of TD, FD, and PD of breeding Anatidae. Using null models, we clarified the relative importance of mechanisms that influence Anatidae community. We also developed random forest models to evaluate the effects of environmental variables on the Anatidae TD, FD, and PD. Our results showed that geographical variation in Anatidae diversity is hemispheric rather than latitudinal. In the species‐rich Northern Hemisphere (NH), the three diversity indices decreased with latitude within the tropical zone of the NH, but increased in the temperate zone reaching a peak at 44.5–70.0°N, where functional and phylogenetic clustering was a predominant feature. In the Southern Hemisphere (SH), Anatidae diversity increased poleward and a tendency to overdispersion was common. In NH, productivity seasonality and temperature in the coldest quarter were the most important variables. Productivity seasonality was also the most influential predictor of SH Anatidae diversity, along with peak productivity. These findings suggested that seasonality and productivity, both consistent with the energy‐diversity hypothesis, interact with the varying histories to shape the contrasting hemispheric patterns of Anatidae diversity. Phylogenetic diversity (PD) and FD underdispersion, widespread across the species‐rich, seasonally productive mid‐to‐high latitudes of the NH, reflects a rapid evolutionary radiation and resorting associated with Pleistocene cycles of glaciation. The SH continents (and southern Asia) are characterized by a widespread tendency toward PD and FD overdispersion, with their generally species‐poor communities comprising proportionately more older lineages in thermally more stable but less predictably productive environments. Abstract : Seasonality and productivity, both consistent with the energy‐diversity hypothesis, interact with the varying histories to shape the contrasting hemispheric patterns of Anatidae diversity. Functional and phylogenetic underdispersion, widespread across the species‐rich, seasonal productive mid‐to‐high latitudes of North Hemisphere, reflects a rapid evolutionary radiation and species resorting associated with Pleistocene cycles of glaciation. The Southern Hemisphere continents (and southern Asia) are characterized by a widespread tendency toward functional and phylogenetic overdispersion, with their generally small faunas comprising proportionately more older lineages in thermally more stable but less predictably productive environments.